Spooky tricks - Wyler, Rose.; Ames, Gerald; Schindler, S. D. ([New York, N.Y.] : HarperTrophy, 1994)
Describes how to write invisible messages, make ghosts appear on walls, and many other tricks.
Keywords: Magic tricks